Feasibility of Mixed Traditional Interview with Multiple Mini-Interviews for Internal Medicine Residency Admission - Sathitruangsak, Chirawadee; Vattanavanit, Veerapong; Intapiboon, Porntip; Pruktanakul, Thakorn; Boonsrirat, Ussanee; Chamroonkul, Naichaya (Education in Medicine Journal, 2026)
This study aimed to evaluate the acceptability and reliability of the mixed traditional interview with multiple mini-interviews (TI-MMI) for resident selection in an internal medicine residency training programme. Data were collected from 34 applicants and 26 interviewers who participated in admission interviews for the training year 2024 of the Internal Medicine Residency Programme at Prince of Songkla University, Thailand. After the four-station mixed TI-MMI, applicants and interviewers were requested to complete an anonymous survey. Cronbach’s alpha and intraclass correlation coefficients were used to evaluate the reliability. Our study showed that most applicants and interviewers considered the mixed TI-MMI a fair and more effective tool to evaluate applicant competencies and preferred the mixed TI-MMI to standard interviews. The interview station reliability (Cronbach’s alpha) ranged from 0.50 to 0.953. Mixed TI-MMI scores demonstrated a significant positive correlation with grade point average (r = 0.44) and National Licence Examination (NLE) scores (r = 0.57). In conclusion, the mixed model of TI-MMI stations for resident admissions is generally feasible, acceptable, and reasonably reliable. However, validated studies should continue to identify the predictive validity of the mixed TI-MMI for selecting residents with the best fit for the programme.